Analisis Perlindungan Hukum atas Penghapusan Merek Tidak Digunakan dalam Putusan MA No. 264 K/Pdt.Sus-HKI/2015 - Maura Viranti A.Syira Adam; Meita Fadhilah (Pusat Riset dan Inovasi Nasional, 2026)
This study examines the legal protection regarding the cancellation of unused trademarks through a case study of the Supreme Court Decision No. 264 K/Pdt.Sus-HKI/2015 between IKEA Systems BV and PT Ratania Khatulistiwa. Trademarks play a vital role in modern trade, functioning not only as product identities but also as guarantees of quality and reputation with significant economic value. Law No. 15 of 2001 stipulates that a trademark may be cancelled if it is not used for three consecutive years, aiming to prevent speculative practices and pseudo-monopolies. However, this provision raises issues when applied to well-known trademarks that require longer periods to penetrate domestic markets. Using a literature review approach, this research analyzes legal norms, doctrines, and court decisions, while comparing them with international practices. The findings reveal that Indonesian law prioritizes the use requirement principle over the global reputation of a trademark. The Supreme Court’s decision to cancel the IKEA trademark demonstrates Indonesia’s legal orientation towards domestic legal certainty, yet it also creates challenges in maintaining a conducive investment climate. Therefore, trademark regulations need to be reformed to become more adaptive to globalization dynamics while balancing the interests of trademark owners, local businesses, consumers, and the state.